Good works : marketing and corporate initiatives that build a better world-- and the bottom line - Kotler, Philip; Hessekiel, David, 1960-; Lee, Nancy, 1945- (Hoboken, New Jersey : Wiley, 2012)
"Marketing guru Philip Kotler, cause marketing authority David Hessekiel, and social marketing expert Nancy Lee have teamed up to create a guide rich with actionable advice on integrating marketing and corporate social initiatives into your broader business goals. Businesspeople who mix cause and commerce are often portrayed as either opportunistic corporate 'causewashers' cynically exploiting nonprofits, or visionary social entrepreneurs for whom conducting trade is just a necessary evil in their quest to create a better world. Marketing and corporate social initiatives requires a delicate balancing act between generating financial and social dividends. Good Works is a book for business builders, not a Corporate Social Responsibility treatise. It is for capitalists with the hearts and smarts to generate positive social impacts and bottom-line business results. Good Works is rich with actionable advice on integrating marketing and corporate social initiatives into your broader business goals. Makes the case that purpose-driven marketing has moved from a nice-to-do to a must-do for businesses Explains how to balance social and business goals Author Philip Kotler is one of the world's leading authorities on marketing; David Hessekiel is founder and President of Cause Marketing Forum, the world's leading information source on how to do well by doing good; Nancy Lee is a corporate social marketing expert, and has coauthored books on social marketing with Philip Kotler With Good Works, you'll find that you can generate significant resources for your cause while achieving financial success"--
Good intentions aren't enough: why some marketing and corporate social initiatives fail and others succeed -- Six social initiatives for doing well by doing good. -- Marketing Driven Initiatives: Growing Sales and Engaging Customers. Cause promoting: persuading consumers to join your company in a good cause ; Cause-related marketing: making contributions to causes based on product sales and consumer actions ; Corporate social marketing: supporting behavior change campaigns. -- Corporate-Driven Initiatives: Expressing and Advancing Your Company's Values and Objectives. Corporate philanthropy: making a direct contribution to a cause ; Community volunteering: employees donating their time and talents ; Socially responsible business practices: changing how you conduct business to achieve social outcomes. -- Offense and Defense. Choosing a social problem to alleviate ; Selecting a social initiative to support the cause ; Developing social initiative programs ; Evaluating efforts ; Summary of best practices ; No good deed goes unpunished: dealing with cynics and critics. -- For Nonprofits and Public Sector Agencies Only. A marketing approach to winning corporate funding and support for social initiatives: ten recommendations.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Marketing -- Social aspects; Social responsibility of business; Relationship marketing; Marketing -- Aspect social; Entreprises; Marketing relationnel; BUSINESS & ECONOMICS -- Marketing -- General; Marketing -- Social aspects; Relationship marketing; Social responsibility of business; dissertations; Academic theses; Academic theses; 2